2022
DOI: 10.1097/med.0000000000000764
|View full text |Cite
|
Sign up to set email alerts
|

Statin therapy is not warranted for a person with high LDL-cholesterol on a low-carbohydrate diet

Abstract: Purpose of reviewAlthough there is an extensive literature on the efficacy of the low carbohydrate diet (LCD) for weight loss and in the management of type 2 diabetes, concerns have been raised that the LCD may increase cardiovascular disease (CVD) risk by increasing the level of low-density lipoprotein cholesterol (LDL-C). We have assessed the value of LDL-C as a CVD risk factor, as well as effects of the LCD on other CVD risk factors. We have also reviewed findings that provide guidance as to whether statin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 284 publications
0
3
0
Order By: Relevance
“…Management of raised LDL-C in individuals adhering to LCDs remains a contentious field, however a growing body of evidence suggests that a default to a statin prescription purely due to a high LDL value, which is independent of a genetic/familial predisposition, may not be appropriate. Indeed, a more comprehensive understanding of LCDs and lipidology has revealed that statin therapy in individuals on an LCD with elevated LDL-C and non-atherogenic lipid profiles (low triglyceride–HDL-C ratios) may not be warranted for primary and secondary prevention of cardiovascular disease ( 15 ). Further research in the form of randomised controlled trials, specifically investigating the long-term effects of CHO-reduction on T1DM lipid profiles is certainly warranted, with an emphasis on cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Management of raised LDL-C in individuals adhering to LCDs remains a contentious field, however a growing body of evidence suggests that a default to a statin prescription purely due to a high LDL value, which is independent of a genetic/familial predisposition, may not be appropriate. Indeed, a more comprehensive understanding of LCDs and lipidology has revealed that statin therapy in individuals on an LCD with elevated LDL-C and non-atherogenic lipid profiles (low triglyceride–HDL-C ratios) may not be warranted for primary and secondary prevention of cardiovascular disease ( 15 ). Further research in the form of randomised controlled trials, specifically investigating the long-term effects of CHO-reduction on T1DM lipid profiles is certainly warranted, with an emphasis on cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important to recognize that the primary reason why LDL-C is a poor marker for CVD risk is because it is a hybrid measure, composed of different sizes of LDL particles (sdLDL and lbLDL), as well as Lp(a) (discussed previously), each with a different association to metabolic health and CVD risk ( 90 , 95 ) [see also Gjuladin-Hellon et al ( 96 ) and Diamond et al ( 97 ) for related review and discussion].…”
Section: Insulin Resistance and Cardiovascular Diseasementioning
confidence: 99%
“…Hence, the pejorative view of LDL-C as the “bad cholesterol,” which has been perpetuated by the disproportionate emphasis on RR statistics, is not supported by a balanced review of the literature. The characteristic of this perspective is the opinion that “evidence falsifying the hypothesis that LDL drives atherosclerosis has been largely ignored” [ 134 ], and the opinion of three cardiologists that “LDL cholesterol risk has been exaggerated” [ 135 ] (see also Ravnskov et al [ 34 ] and Diamond et al [ 136 ] for related reviews and discussion).…”
Section: Reviewmentioning
confidence: 99%